Remarkable enhancement of Fe–V–Ox composite metal oxide to gold catalyst for CO oxidation in the simulated atmosphere of CO2 laser. Issue 62 (8th August 2017) - Lin, Qingquan; Han, Chun; Su, Huijuan; Sun, Libo; Ishida, Tamao; Honma, Tetsuo; Sun, Xun; Zheng, Yuhua; Qi, Caixia
Abstract : A novel Au/Fe–V–O x /Al2 O3 displays remarkable activity and good stability for CO oxidation in simulated atmosphere of CO2 laser. The higher Au dispersion and more labile lattice oxygen after modification contributed to its outstanding performance. Abstract : A novel Au/Fe–V–O x /Al2 O3 catalyst displayed remarkable activity and good stability for CO oxidation in the simulated atmosphere of a CO2 laser with high CO2 levels up to 60 vol% and stoichiometric or even lower O2 /CO ratio. The improved surface labile lattice oxygen on the FeO x and VO x modified Al2 O3 plays a crucial role in its outstanding performance for the CO oxidation reaction in an oxygen-poor atmosphere.